The Attribution of Human Seasonal Influenza H3N2 Virus Detection to the Collector, Not Avian Sources, During the 2022 Highly Pathogenic Avian Influenza Outbreak in Pennsylvania, USA—Implications for Biosafety and Biosecurity - Deepanker Tewari; Manoj K. Sekhwal; Mary L. Killian; Corey Zellers; Chrislyn Wood Nicholson; Betsy Schroeder; Erica Spackman; Alex Hamberg (Zoonotic Diseases)
Highly pathogenic avian influenza (HPAI) surveillance for influenza A virus (IAV) in the United States is conducted using a National Animal Health Laboratory Network (NAHLN) real-time reverse transcriptase–polymerase chain reaction (rRT-PCR). Samples showing the presence of IAV are confirmed and characterized at the national reference laboratory. During the H5N1 HPAI outbreak in 2022, our laboratory reported the detection of IAV in a PA commercial chicken flock using rRT-PCR targeting the matrix gene, which was negative for the H5/H7 subtypes. IAV was not detected by additional sampling of the birds the following day with rRT-PCR. The virus detected was characterized as a human seasonal H3N2 with whole-genome sequencing (WGS). Further investigation revealed that the collector who visited the farm was diagnosed with an IAV infection. This case report emphasizes the importance of farm biosafety and biosecurity, of conducting regular reviews of worker safety protocols, and of advanced molecular techniques like WGS for viral characterization and epidemiology.